Development of a delinquent customer management model using DMAIC steps and KPIs at a Service Station - Altamirano-Miranda, Giuliano; Armas-Rubio, Treicy; Elías-Giordano, Cynthia; Torres-Sifuentes, Carlos; Cespedes, Carlos (LACCEI, 2023)
The objective of this work is to propose a customer management model to address the high delinquency existing in a company dedicated to the retail sale of fuel. The study followed an approach based on DMAIC (Define, Measure, Analyze, Improve and Control) steps to address customer delinquency. The company’s current credit and collection policies were identified, as well as the current indicators of the process. Then, the information obtained was analyzed to propose the implementation of new management KPIs, a restructuring of policies and a training plan for staff. In the control stage, the new indicators implemented were applied in order to maintain continuous monitoring of improvements, as well as a training schedule. This model makes it possible to correctly manage credit and collection policies and processes involved in the existence of a high number of delinquent clients, in such a way that said processes can be redefined, as well as achieving a reduction in the number of clients who do not pay off their debt. within the established time and become part of the company’s delinquent portfolio. The motivation for this work is to establish a management model for delinquent customers, which serves as a guide for the various companies belonging to the retail fuel sector.